2020
DOI: 10.1016/j.jpainsymman.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Center Observational Review of Hospital-Based Palliative Care in Patients Dying With COVID-19

Abstract: The current coronavirus disease 2019 (COVID-19) pandemic has put significant strain on all aspects of health care delivery, including palliative care services. Given the high mortality from this disease, particularly in the more vulnerable members of society, it is important to examine how best to deliver a high standard of end-of-life care during this crisis. This case series collected data from two acute hospitals examining the management of patients diagnosed with COVID-19 who subsequently died (n ¼ 36) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 9 publications
0
43
2
9
Order By: Relevance
“…Patients with serious COVID-19 with persistent symptoms and concerns despite optimal disease treatment need optimal symptom management [ 15 ]. It has been suggested that symptom burden in dying patients with COVID-19 might be higher than usual in dying patients without COVID-19 [ 32 ], resulting in challenges for staff with no or limited experience in palliative care. Therefore, palliative care has an important role for patients with serious COVID-19 and strategies have been implemented to provide in-hospital palliative care [ 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with serious COVID-19 with persistent symptoms and concerns despite optimal disease treatment need optimal symptom management [ 15 ]. It has been suggested that symptom burden in dying patients with COVID-19 might be higher than usual in dying patients without COVID-19 [ 32 ], resulting in challenges for staff with no or limited experience in palliative care. Therefore, palliative care has an important role for patients with serious COVID-19 and strategies have been implemented to provide in-hospital palliative care [ 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…An early case series of 101 hospitalised patients with covid-19 who were referred to palliative care found that opioids were usually effective for palliation of breathlessness, with a median dose of 10 mg (range 5-30 mg) subcutaneous morphine over 24 hours 10. A retrospective audit of 36 hospitalised patients with covid-19 who died outside critical care found that 26 of them had a subcutaneous infusion at the time of death, and the total mean opioid dose (subcutaneous morphine equivalent) during the final 24 hours was 16 mg 13…”
Section: How Can Breathlessness In Severe Covid-19 Be Managed?mentioning
confidence: 99%
“…6 Only recently has evidence emerged to help characterise symptom burden and outcomes in end stage COVID-19, but with small patient numbers and focussed geographical locations. [7][8][9] Our primary aim was to further characterise the symptom profile, outcomes and symptom management requirements of hospitalised patients with COVID-19 referred to Hospital Palliative Care. Our secondary aim was to contextualise Palliative Care demands from COVID-19 against a 'typical' Palliative Care caseload pre-pandemic.…”
Section: Introductionmentioning
confidence: 99%